PELATIHAN MENJADI BILAL DAN KHATIB BAGI REMAJA MASJID AL-MUHAJIRIN DESA JAYASAMPURNA - Nursahid, Catur Febri; Mulyadi, Acep; Irham, Irham (An-Nizam, 2024)
The purpose of this training is to provide an understanding to mosque teenagers regarding how to be a good bilal and khatib and to find solutions to existing problems related to the lack of of appearance of teenagers in the mosque. The training was conducted in the form of training on how to be a bilal and khatib for teenagers in Jayasampurna Village, Serang Baru District, Bekasi Regency. The formulationof the problems raised in this training is related to the function of the bilal and preacher which is very important in Islamic preaching, so that the preacher must be delivered in a language that is easily understood by the congregation, except for the pillars of the preacher. In addition, the increase in the quantity of mosques also creates new problems, especially for the bilal and khutbah. Currently, bilal and khatib are still dominates by the older generation. To find alternative solutions to the above problems, a training program was held to become bilal and khatib for teenagers in Jayasampurna Village. The targets of this training were 23 teenagers consisting of 19 male teenagers and 4 female teenagers. The results of this activity are (1) providing an understanding to mosque teenagers about how to become a good and correct bilal and khatib (2) giving confidence to teenagers when becoming a bilal and khatib (3) being one the solutions for mosque administrators when they want to carry out Friday prayers by empowering local residents.